Cambridge lower secondary English workbook 7 - Elsdon, Graham (United kingdom : Cambridge university press, 2021)
The Cambridge Lower Secondary English Workbook 7 is a complementary resource to the Learner's Book 7 and is designed to provide additional practice and reinforcement of the skills learned. It focuses on developing students$1 (BEnglish proficiency through a variety of exercises that cover grammar, vocabulary, reading comprehension, writing, and speaking.s
Keywords: English : Workbook